- #1

- 1,367

- 61

## Main Question or Discussion Point

Hello,

I have the following summation:

[tex]\sum_{l=0}^Lb_l\exp\left(-j\frac{2\pi}{N}kl\right)[/tex]

If

[tex]b_1=\cdots b_L=b[/tex]

then by making L=N-1 the above summation will be zero. Now, if the coefficients are not equal, can we make the summation zero, and how?

Thanks

I have the following summation:

[tex]\sum_{l=0}^Lb_l\exp\left(-j\frac{2\pi}{N}kl\right)[/tex]

If

[tex]b_1=\cdots b_L=b[/tex]

then by making L=N-1 the above summation will be zero. Now, if the coefficients are not equal, can we make the summation zero, and how?

Thanks